The role of cultural proximity on preference of Chinese Malaysians in Chinese film - Kang, Hongzhe; Yasin, Megat Al Imran; Osman, Mohd Nizam; Ang, Lay Hoon; Li, Mengyu (Human Resource Management Academic Research Society, 2021)
This paper is to identify the cultural factors that contribute to the preference of Chinese Malaysians in Chinese films that attempt to maintain their cultural identity in the multicultural context of Malaysia. Because of the historical and cultural relationship between Chinese Malaysians and Chinese, cultural proximity was used as the main theory to determine the factors that preference of Chinese Malaysians in Chinese films. This study focused on Chinese Malaysian students from Universiti Putra Malaysia (UPM) and applied semi-structured interviews in qualitative research methods. Moreover, this study found that language and education, customs and festivals, religion and lifestyle, arts were the main factors influencing Chinese Malaysians' preference for Chinese films.